Regime-Switching Market Risk: Evidence from the Philippines - Yu, Joel C.; Goyeau, Daniel; Bautista, Carlos C. (Philippine Management Review; Vol 18 (2011), 2011)
This paper presents an alternative approach in measuring time variation in market risk. Using equity returns in the Philippines, we employ a Markov-switching model to estimate market risk that varies with occasional and discrete shifts in states. Results show that the technique is a productive alternative in evaluating the market risk of firms in the Philippines. Shifts in the market risk seem to be related to market developments, which can have a permanent or transient change in the volatilities of security returns relative to that of the market.
Keywords: Markov-switching; time-varying betas; market risk; CAPM